Walking for environmental health - Buan, Aivi R. (Asia Life Sciences : the Asian International Journal of Life Sciences, 2008)
Modern lifestyle pays little attention to the importance of physical activity in the guise of busy schedules. This is tragic since the human body demands certain forms of physical activity to support the metabolic processes that sustain a healthy life. This study examines the various types of walking, which could be a very good introduction to the value of exercise and how much each could impact to certain fitness parameters specifically cardiovascular endurance. Results show that strolling due to its more relaxing pace is a good activity for maintaining physical fitness while brisk walking and athletic walking are activities that are more appropriate if one's objective is to improve physical fitness. Engaging in walking results not only in improved physical fitness, but also serves as a good entry point to advocate environmental awareness because a heightened concern for good health relates to realizing that man is part of the environment and thus contributes to acting as good stewards of the environment.